THE PROFILE OF STUDENTS' LEARNING STYLES AND THEIR EFFECTS ON GRADE POINT AVERAGE (GPA) ACHIEVEMENT - Keliat, Natalia Rosa (Prodi Teknologi Pendidikan, 2016)
Abstract. Learning style is one of the important factors needed to absorb, store and process the new information. This research is a study to see the profile and percentage of studenst learning styles of SWCU Biology Education students and the influence of different learning styles on the GPA obtained. Researcher got the data of students’ learning styles by using questionnaire. The statistical procedures employed in this study were one-way ANOVA. The results showed that the largest percentage of learning styles that were used by the students of biology education were auditory learning styles by 32% and the VAK (Visual Auditory Kinesthetic) learning style was the least used by education students by 2%. The analysis of the percentage of learning styles showed that 72% of students with auditory learning styles reached a satisfactory category until magna cum laude, but the percentage of students that used VAK (Visual Auditory Kinesthetic ) learning styles only reached satisfying GPA level. Statistical test results in this study demonstrated that the use of learning styles did not give significantly different effect on the students’ GPA.Keywords: Personal Learning Styles, Grade Point Average Abstrak. Gaya belajar adalah salah satu faktor penting yang diperlukan untuk menyerap, menyimpan dan memproses informasi baru. Penelitian ini adalah suatu penelitian untuk melihat profil dan persentase gaya belajar mahasiswa pendidikan biologi UKSW serta pengaruh gaya belajar yang berbeda terhadap indeks prestasi kumulatif yang diperoleh. Peneliti mendapatkan data gaya belajar mahasiswa dengan menggunakan kuesoner (angket). Prosedur statistik yang digunakan dalam penelitian ini adalah one way ANOVA. Hasil penelitian menunjukkan bahwa persentase gaya belajar terbesar yang digunakan mahasiswa pendidikan biologi untuk belajar adalah gaya belajar auditorik sebanyak 32%, Persentase gaya belajar yang paling sedikit digunakan oleh mahasiswa pendidikan adalah gaya belajar VAK (Visual Auditorik Kinestetik) sebanyak 2%. Analisis persentase gaya belajar menunjukkan persentase mahasiswa pendidikan biologi dengan gaya belajar auditorik adalah yang terbanyak memiliki IPK yang termasuk dalam kategori memuaskan sampai magna cum laude sebesar 72%, namun ternyata persentase mahasiswa dengan gaya belajar VAK (Visual Auditorik Kinestetik) tidak mencapai IPK memuaskan, dan hanya mencapai level kurang. Hasil uji statistik dalam penelitian ini menunjukkan penggunaan gaya belajar tidak memberikan pengaruh yang berbeda secara signifikan terhadap indeks prestasi kumulatif mahasiswa.Kata Kunci : Gaya Belajar, Indeks Prestasi Kumulatif